Presence of anti-Leishmania infantum antibodies in sheep (Ovis aries) in Spain - Sergio Villanueva-Saz; María Eugenia Lebrero; Alba Solsona; Juan José Ramos; Marta Ruíz de Arcaute; Héctor Ruíz; María D. Pérez; José María Bello; Maite Verde; Aurora Ortín; Diana Marteles; Antonio Fernández; et al. (Veterinary Research Communications, 2024)
Sandflies are the primary transmission vector for Leishmania spp parasite in endemic regions. The role of other animals, different from the dog, is under discussion in the leishmaniosis endemic countries. A limited number of reports have been published on the possible role of livestock in European countries for Leishmania maintenance and diffusion. The aim of the present study was to perform a serosurvey on sheep in areas of Spain that are endemic for zoonotic leishmaniosis and establish the possible role of sheep regarding Leishmania infantum infection in endemic areas. Three hundred and two serum samples were obtained from sheep and were evaluated for serological survey to detect L. infantum by using the in-house ELISA technique. Twenty-eight out of the 302 samples included in this study, were positive for L. infantum antibodies (9.27%). In the present study, a significant association was found between adult age and seropositivity (p = 0.006) and female gender and seropositivity (p = 0.02). This association has not been previously described in other European studies related to L. infantum infection in sheep. Our study reveals that domestic sheep in a European Mediterranean country are exposed to L. infantum . To our knowledge, this study demonstrates the presence of seropositive sheep in different regions of Spain for the first time. Further epidemiological studies focus on evaluating the rural cycle of this parasite to know if livestock could act as a potential reservoir are needed.